Primary cutaneous CD4+ pleomorphic small to medium cell T cell lymphoma: a clinical case - N. V. Zilberberg; M. M. Kokhan; G. D. Safonova; O. G. Rimar; I. A. Kuklin; V. A. Iglikov (Лечащий Врач)
The diagnosis of primary cutaneous CD4+ pleomorphic T-cell lymphoma of the skin from small and medium-sized cells is difficult due to the rare occurrence of this nosology. The disease must be differentiated from primary B-cell lymphoma of the skin, anaplastic large cell CD30+ skin lymphoma, tumor stage of fungal mycosis, pseudolymphoma. The importance of clinical oncological alertness of doctors and the need for clinical and laboratory examination of a patient using modern histological and immunohistochemical research methods are shown. The article presents a case of diagnostics of a rare variant of primary skin lymphoma of cellular skin lymphoma – primary cutaneous CD4+ small/medium sized pleomorphic T-cell lymphoma in a 70-year-old patient. The diagnosis was verified by pathomorphological and immunohistochemical studies of the biopsy of the affected skin.